ON THE NUMBER OF VERTICES WITH AN INTERVAL SPECTRUM IN EDGE LABELING OF REGULAR GRAPHS - Davtyan, N.N.; Kamalian, R.R (Proceedings of the YSU A: Physical and Mathematical Sciences, 2014)
Undirected simple finite graphs are considered. An upper bound of the number of vertices with an interval spectrum is obtained for any edge labeling of an arbitrary regular graph.